2019
DOI: 10.1108/ijoem-05-2018-0263
|View full text |Cite
|
Sign up to set email alerts
|

The mediating impact of demonetisation on customer acceptance for IT-enabled banking services

Abstract: Purpose The purpose of this paper is to explore the mediating role of demonetisation in the usage of IT-enabled banking services (ITeBS). The study extends the theory of technology readiness (TR) (Parasuraman and Colby, 2015) by incorporating the behavioural intention and actual usage of ITeBS. Design/methodology/approach Based on the theory of TR and encompassing the impact of demonetisation, the study examines the functional relationship of TR, behavioural intention and actual usage. Structural equation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…The statistical results of the study confirmed the significant positive direct effect of the PU, PEOU and AS on the adoption of Islamic banking. These results of the study were found similar to the studies on the adoption of the Mobile, Online and Credit cards of the Islamic banking (Durkin et al, 2008;Amin, Abdul-Rahman and Abdul-Razak, 2013;Leonhardt and Chu, 2017;Aziz and Afaq, 2018;Warsame and Ireri, 2018;Kansal and Chaganti, 2018;Shareef et al, 2018;Charag, Fazili and Bashir, 2019;Hussain et al, 2019;Jünger and Mietzner, 2019;Nagdev, Rajesh and Misra, 2019;Talwar et al, 2020). The study found significant increase in the adoption behavior of the users in the Bottom of the Pyramid market when the advertising spend was interacted in the model as moderator.…”
Section: Discussionsupporting
confidence: 84%
“…The statistical results of the study confirmed the significant positive direct effect of the PU, PEOU and AS on the adoption of Islamic banking. These results of the study were found similar to the studies on the adoption of the Mobile, Online and Credit cards of the Islamic banking (Durkin et al, 2008;Amin, Abdul-Rahman and Abdul-Razak, 2013;Leonhardt and Chu, 2017;Aziz and Afaq, 2018;Warsame and Ireri, 2018;Kansal and Chaganti, 2018;Shareef et al, 2018;Charag, Fazili and Bashir, 2019;Hussain et al, 2019;Jünger and Mietzner, 2019;Nagdev, Rajesh and Misra, 2019;Talwar et al, 2020). The study found significant increase in the adoption behavior of the users in the Bottom of the Pyramid market when the advertising spend was interacted in the model as moderator.…”
Section: Discussionsupporting
confidence: 84%
“…rapid adoption of digital payment instruments, including banking cards, mobile wallets, mobile banking, internet banking and other digital payment modes (Chaurasia et al, 2019;Goriparthi and Tiwari, 2017;Mohd, 2016;PWC, 2020, Nagdev et al, 2021. With a vision to transform India from traditional 'cash-based economy' into a 'cashless economy' and also as part of the 'Digital India' initiative, GoI has promulgated the digital payments system as a result of promoting cashless transactions (Midthanpally, 2017;Pachare, 2016;Sobti, 2019).…”
mentioning
confidence: 99%
“…AI is also helping develop vital social skills for children with disabilities (Hinsch et al, 2020). AI-powered solutions have been at the forefront of the exponential growth saga of e-commerce and retail, and the researchers identified this gap (Nagdev et al, 2021). This current study plans to pinpoint the different sectors of retail using AI tools (see Table 5) in different stages of customer journey mapping and depict the same by a framework (see Figure 2).…”
Section: Theoretical Basismentioning
confidence: 99%
“…, 2020). AI-powered solutions have been at the forefront of the exponential growth saga of e-commerce and retail, and the researchers identified this gap (Nagdev et al. , 2021).…”
Section: Theoretical Basismentioning
confidence: 99%